Religious Harmony and Identity Politics in Indonesia’s Electoral Democracy - Sandra Leoni Prakasa Yakub; Santi Suryani; Faisal Fadilla Noorikhsan; Muhamad Reza Atqia; Novia Laela (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This research is driven by the increasing strength of religion-based identity politics in Indonesia’s post-reform electoral democracy, which creates a dilemma between legitimate political competition and threats to interfaith harmony. The problem formulation of this study concerns how identity politics challenges religious harmony and to what extent harmony can serve as an instrument to reduce polarization and reinforce democratic consolidation. The research questions focus on two main aspects: (1) how the dynamics of harmony are tested by the exploitation of religious issues within electoral contests, and (2) how harmonization strategies can function as social capital in maintaining democratic stability. Using a qualitative approach with a juridical-normative and socio-political framework, this study relies on a literature review involving laws and regulations, court decisions, official state documents, and national and international academic works, combined with content analysis of religiously nuanced political narratives in media and public discourse. The findings indicate that harmony is not a natural social condition but a socio-political construction that is vulnerable to instrumentalization by electoral interests. FKUB and harmony-related regulations tend to remain normative and less effective in the absence of substantive justice. Nonetheless, harmony still holds potential as strategic capital for democracy if it is developed through a framework of justice, religious political literacy, and inclusive democratic governance.